Formulation and Evaluation of Hydrocarbon Ointment from 96% Ethanol Extract of Red Tender Leaves (Syzygium myrtifolium Walp.) - Stiyani, Rintika Isa; Mutripah, Siti; Rahayu, Nila Rusdi; Badriyah, Lailatul; Alfiza, Ibnu Syinna (Pustaka Media Publishing, 2025)
Red Shoot Leaf (Syzigium myrtifolium Walp) has chemical compounds of alkaloids, steroids, triterpenoids, flavonoids, phenolics, and saponins, and has the antibacterial effect of Staphylococcus aureus. This study aims to find out whether Red Shoot leaf extract can be formulated in ointment preparations with hydrocarbon bases and determine the opimal formulation based on physical evaluation. The research was conducted using an experimental method. Red Shoot leaf extract (Syzigium myrtifolium Walp) was obtained by maceration using 96% ethanol solvent. The extract is formulated into an ointment preparation with three different formulas, namely formula 1 with a variation in the concentration of cera alba 4%, formula 2 with a concentration of cera alba 8% and formula 3 with a concentration of cera alba 12%. The results of the ointment preparations were then evaluated organoleptically, homogeneity, pH, and dispersibility. Based on the results obtained in the spreadability test, it has decreased. The preparation that has the greatest dispersion is found in formula I where the concentration of cera alba used is 4%, while the lowest dispersion is found in formula III with a concentration of cera alba of 12%. Meanwhile, judging from the evaluation of organoleptic, homogeneity, and pH, the three formulas have met the requirements. It can be concluded that 96% ethanol extract of Red Shoot leaves (Syzigium myrtifolium Walp) can be formulated into hydrocarbon ointment preparations and meet the optimal formula requirements, namely 4% and 8% alba cera concentrations.